ANALYSIS OF FACTORS AFFECTING EMERGENCY FUND MANAGEMENT IN THE COMMUNITY OF TERBANGGI MARGA VILLAGE, SUKADANA, LAMPUNG EAST - Selin Jurniasari; Thoyibatun Nisa; Era Yudistira (Universitas Muhammadiyah Tangerang, 2026)
Emergency funds are an essential component of household financial resilience, particularly in rural communities that are vulnerable to income fluctuations and economic uncertainty. Limited financial preparedness in such settings highlights the importance of identifying key factors that influence emergency fund management. This study aims to analyze the effects of financial literacy, financial experience, lifestyle, and online lending on emergency fund management among residents of Terbanggi Marga Village. This research employed a quantitative approach using survey data collected from 89 respondents selected through purposive sampling, meaning respondents were chosen based on specific criteria relevant to the research objectives. The data were analyzed using multiple linear regression to examine the individual and combined effects of the independent variables on emergency fund management. The results show that financial literacy (p = 0.001) and financial experience (p = 0.001) have a positive and statistically significant effect on emergency fund management. In contrast, lifestyle (p = 0.692) and online lending (p = 0.411) do not demonstrate a significant influence. The simultaneous effect of all independent variables is confirmed by the F-test, which assesses their joint impact on the dependent variable (p = 0.001). Furthermore, the coefficient of determination (RÂ² = 0.698) indicates that the regression model explains 69.8% of the variation in emergency fund management. These findings suggest that improving financial literacy and strengthening financial experience are critical strategies for enhancing emergency fund management in rural communities, while lifestyle patterns and the use of online lending services appear to play a less dominant role